2016
DOI: 10.1080/07391102.2016.1172026
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of glucosepane–water and hydrogen bond formation: an electron topology and orbital analysis

Abstract: Leeuw (2017) Computational study of glucosepane-water and hydrogen bond formation: an electron topology and orbital analysis, Journal of Biomolecular Structure and Dynamics, 35:5, 1127-1137, DOI: 10.1080/07391102.2016 The collagen protein provides tensile strength to the extracellular matrix in addition to localising cells, proteins and protein cofactors. Collagen is susceptible to a build up of glycation modifications as a result of an exceptionally long half-life. Glucosepane is a collagen cross-linking ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…1 and Supplementary note 1). Previous work has demonstrated that glucosepane is very hydrophilic [ 27 ] and may therefore be responsible for the higher water content detected in the tendon tissue from old donors.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…1 and Supplementary note 1). Previous work has demonstrated that glucosepane is very hydrophilic [ 27 ] and may therefore be responsible for the higher water content detected in the tendon tissue from old donors.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Water molecules are implicated in many important biological processes (de Beer, Vermeulen, & Oostenbrink, 2010;Likic, Juranic, Macura, & Prendergast, 2000;Nash, Saßmannshausen, Bozec, Birch, & de Leeuw, 2017;Uroshlev et al, 2016). The crystal structures of FABP5 (pdb id 1B56) and CRABP-II (pdb id 2CBS) had water molecules present: 39 water molecules in the FABP5 crystal structure, 6 of which are within 4 Å of the bound ligand, and 53 water molecules in the CRABP-II crystal structure, only 2 of which are within 4 Å of the bound ligand.…”
Section: Trapped Water Moleculesmentioning
confidence: 99%
“…31 The ωB97X-D functional has been employed to study systems where hydrogen bonds play a relevant role. 32,33 We characterized the nature of the stationary points according to their second order Hessian matrix: minimum energy points on the potential energy surface showed only positive eigenvalues and transition states showed one and only one negative eigenvalue. Implicit solvation was considered in all steps with the self-consistent reaction field (SCRF) option of Gaussian09, using the integral equation formalism variant of the polarizable continuum model (IEFPCM) 34,35 with water (ε = 78.35) as solvent.…”
Section: Methodsmentioning
confidence: 99%